The fiddler crab, Minuca pugnax, follows Bergmann's rule. Issue 24 (9th December 2019) - Johnson, David Samuel; Crowley, Cynthia; Longmire, Katherine; Nelson, James; Williams, Bethany; Wittyngham, Serina
Abstract: Bergmann's rule predicts that organisms at higher latitudes are larger than ones at lower latitudes. Here, we examine the body size pattern of the Atlantic marsh fiddler crab, Minuca pugnax (formerly Uca pugnax), from salt marshes on the east coast of the United States across 12 degrees of latitude. We found that M. pugnax followed Bergmann's rule and that, on average, crab carapace width increased by 0.5 mm per degree of latitude. Minuca pugnax body size also followed the temperature–size rule with body size inversely related to mean water temperature. Because an organism's size influences its impact on an ecosystem, and M. pugnax is an ecosystem engineer that affects marsh functioning, the larger crabs at higher latitudes may have greater per‐capita impacts on salt marshes than the smaller crabs at lower latitudes. Abstract : The fiddler crab, Minuca pugnax, follows Bergmann's rule, with the largest crabs at the highest latitudes. M. pugnax body size was negatively correlated with water temperature, following the temperature–size rule.